LAPORAN KETERANGAN PERTANGGNGJAWABAN AKHIR MASA JABATAN (LKPj) GUBERNUR BANTEN PERIODE 2012-2017 (Suatu Tinjauan) - Toni Anwar Mahmud (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2020)
As per the laws and regulations the regional government is obliged to submit a statement of accountability at the end of the term of office. The report contains information on the implementation of Decentralization, Co-Administration and Public Administration. The methodology in this research was carried out by the method of library study (documentary study) to collect data and information. The documentation study was carried out by conducting a comparative study of policy documents that became legal references, including: (1) Regional Medium-Term Development Plan (RPJMD) 2012-2017, (2) Banten Provincial Regulation Number 3 of 2015 Concerning Changes Banten Province Regional Revenue and Expenditure Budget 2015 and (3) Official BPS News. The results of the study found that the information conveyed in the report did not adjust to the indicators, benchmarks and achievements as stated in the 2015 RKPD. There was no visible relationship between vision, mission, goals and performance achievements in 2015. The performance of the Banten provincial government in general, have not yet achieved the vision and mission stated in the 2012-2017 RPJMD document.